Mediatisasi Kebijakan Penerbitan E-Journal dengan Open Journal System di Indonesia - Wahid Nashihuddin (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Every technology and media carries its message for users and brings change in human life, including e-journal publishing. The practice of modernization in the e-journals publishing by OJS also has an impact on changing the journal appearance and the publishing process, starts from the manuscript submission by the author, editorial, and peer-reviewed, to journal publishing by the editor. Printed journals that are formed of paper sheets and have limited information access are different from e-journals that are formed of digital files and information access is not limited (online). The government policies regarding the OJS existence and function as one of the standard e-journal publishing platforms in Indonesia and the accreditation requirements of national scientific journals, also have an impacted on the behavior and culture-changing of the users (writers, editors, reviewers, proofreaders) and enhancing the scholarly communication culture. OJS as technology or media has become a mediation for its users and has even been institutionalized by the government, and this phenomenon has become one of mediation in journal publishing. This paper aims to find out the mediation of government policies related to the issuance of e-journals using OJS in Indonesia. The study data is descriptive-qualitative, with the source of literature study data and the best practice knowledge of the author. This study shows that government policies related to the use of OJS for e-journal publishing in Indonesia effect on changes in the appearance and process of journal publishing, changes in user behavior and culture, and improvement in scholarly communication culture.